Genomic analysis of the evolutionary lineage of Norovirus GII.4 from archival specimens during 1975–1987 in Tokyo. Issue 2 (13th July 2016) - Mori, Kohji; Chu, Pei‐Yu; Motomura, Kazushi; Somura, Yoshiko; Nagano, Miyuki; Kimoto, Kana; Akiba, Tetsuya; Kai, Akemi; Sadamasu, Kenji
Abstract : This study aimed to analyze NoV GII.4 sequences from archival specimens obtained during 1975–1987 by comparing them with reference sequences. The first NoV GII.P4_GII.4 sequence was identified in 1980. NoV GII.4 collected in 1970 had a GII.P1_GII.4 sequence. These results indicate that the GII.P4_GII.4 sequence may be the result of a recombination that might have occurred around 1980. Amino acid substitutions based on this replacement were mainly accumulated in the NTPase, p22, and RdRp regions. The emergence of GII.P4_GII.4 sequence is considered to have ended the major prevalence of NoV GII.4. J. Med. Virol. 89:363–367, 2017 . © 2016 Wiley Periodicals, Inc.